Conflict managment in the international organization - Novik, I. O. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article is devoted to the fact that conflicts are inevitable in our lives and that conflict management in the international organization is one of the most important areas in the activities of the head because it affects the productivity of employees and it affects the results of the work of the organization as a whole. The article discusses the mechanisms of management as well as the definition of conflict and how to manage stress to avoid conflict situations in the organization. For most companies, the main reason was and remains a conflict of interest of employees, and that would prevent or resolve an existing conflict the article reveals the stages of conflict development and the characteristics of ways to resolve conflicts, as well as methods of behavior of individuals or groups in the conflict, called methods of conflict prevention in the organization, reveals what is conflict forecasting since it plays a not unimportant role in personnel management in the organization. To resolve conflict situations, the leader can turn to methods such as smoothing, cooperation, compromise, etc. The use of these strategies can help resolve conflicts. One of the most effective methods of conflict resolution is a compromise, since most often the conflicting parties use a compromise, since the friendly steps towards which one of the conflicting parties makes, make it possible to achieve an asymmetric (one side can give in more, the other will give in less) or even symmetrical ( parties are trying to make mutual concessions approximately equal to each other) agreement. The main thing to remember is that managing conflicts between employees is a controlled process, and even people with opposite views on the situation can agree. And do not forget about the prevention and forecasting of conflicts in order to prevent the appearance of discontent and tension in the team. Conclusions based on the results of the study are formulated.

Стаття присвячена тому що конфлікти неминучі в нашому житті і управління конфліктами в міжнародній організації є одним з найважливіших напрямків в діяльності керівника адже від цього залежить продуктивність співробітників і це впливає на результати роботи організації в цілому. У статті були розглянуті механізми управління а також визначення конфлікту, фактори, які спричиняють стрес і як управляти стресом з метою уникнення конфліктних ситуацій в організації. Для більшості компаній основною причиною був і залишається конфлікт інтересів співробітників, і що б це запобігти або дозволити вже наявний конфлікт у статті розкриваються етапи розвитку конфлікту та характеристика способів вирішення конфліктів, вказані так само методи поведінки індивідуумів або груп у конфлікті, назвали методи профілактики конфліктів в міжнародній організації, розкривається що таке прогнозування конфліктів так як воно грає не маловажну роль в управлінні персоналом в організації. Для вирішення конфліктних ситуацій керівник може звернутися до таких методів як згладжування, співпраця, компроміс та ін. Використання цих стратегій може сприяти вирішенню конфліктів. Одним із найефективніших методів вирішення конфлікту є компроміс, оскільки найчастіше конфліктуючі сторони використовують компроміс, оскільки дружні кроки назустріч, які робить одна з конфліктуючих сторін, дозволяють досягти асиметричного (одна сторона може поступитися більше, інший поступиться менше) або навіть симетрична ( сторони намагаються зробити приблизно рівні один одному взаємні поступки) угоду. Головне пам'ятати, що управління конфліктами між співробітниками — керований процес, і домовитись можуть навіть люди з протилежними поглядами на ситуацію. І не забувайте про профілактику та прогнозування конфліктів, щоб не допустити появи невдоволення та напруженості в колективі. Сформульовані висновки за результатами проведеного дослідження.
Управління конфліктами в міжнародній організації
Keywords: conflict; stages of conflict; conflict prevention; organizational conflict; конфлікт; етапи розвитку конфлікту; запобігання конфліктам; організаційний конфлікт